ANTARES Search for Point Sources of Neutrinos Using Astrophysical Catalogs: A Likelihood Analysis (ANTARES Collaboration), and - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Astrophysical Journal, 2021)
A search for astrophysical pointlike neutrino sources using the data collected by the ANTARES detector between 2007 January 29 and 2017 December 31 is presented. A likelihood method is used to assess the significance of an excess of muon neutrinos inducing track-like events in correlation with the location of a list of possible sources. Different sets of objects are tested in the analysis: (a) a subsample of the Fermi 3LAC catalog of blazars, (b) a jet-obscured population of active galactic nuclei, (c) a sample of hard X-ray selected radio galaxies, (d) a star-forming galaxy catalog, and (e) a public sample of 56 very-high-energy track events from the IceCube experiment. None of the tested sources shows a significant association with the sample of neutrinos detected by ANTARES. The smallest p-value is obtained for the catalog of radio galaxies with an equal-weights hypothesis, with a pre-trial p-value equivalent to a 2.8σ excess, which is equivalent to 1.6σ post-trial. In addition, the results of a dedicated analysis for the blazar MG3 J225517+2409 are also reported: this source is found to be the most significant within the Fermi 3LAC sample, with five ANTARES events located less than one degree from the source. This blazar showed evidence of flaring activity in Fermi data, in spacetime coincidence with a high-energy track detected by IceCube. An a posteriori significance of 2.6σ for the combination of ANTARES and IceCube data is reporte

Deep-sea deployment of the KM3NeT neutrino telescope detection units by self-unrolling - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of Instrumentation, 2020)
KM3NeT is a research infrastructure being installed in the deep Mediterranean Sea. It will house a neutrino telescope comprising hundreds of networked moorings - detection units or strings - equipped with optical instrumentation to detect the Cherenkov radiation generated by charged particles from neutrino-induced collisions in its vicinity. In comparison to moorings typically used for oceanography, several key features of the KM3NeT string are different: the instrumentation is contained in transparent and thus unprotected glass spheres; two thin Dyneema (R) ropes are used as strength members; and a thin delicate backbone tube with fibre-optics and copper wires for data and power transmission, respectively, runs along the full length of the mooring. Also, compared to other neutrino telescopes such as ANTARES in the Mediterranean Sea and GVD in Lake Baikal, the KM3NeT strings are more slender to minimise the amount of material used for support of the optical sensors. Moreover, the rate of deploying a large number of strings in a period of a few years is unprecedented. For all these reasons, for the installation of the KM3NeT strings, a custom-made, fast deployment method was designed. Despite the length of several hundreds of metres, the slim design of the string allows it to be compacted into a small, re-usable spherical launching vehicle instead of deploying the mooring weight down from a surface vessel. After being lowered to the seafloor, the string unfurls to its full length with the buoyant launching vehicle rolling along the two ropes. The design of the vehicle, the loading with a string, and its underwater self-unrolling are detailed in this paper.
CRIS-Team WoS Importer:2020-12-18

Monte Carlo simulations for the ANTARES underwater neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Monte Carlo simulations are a unique tool to check the response of a detector and to monitor its performance. For a deep-sea neutrino telescope, the variability of the environmental conditions that can affect the behaviour of the data acquisition system must be considered, in addition to a reliable description of the active parts of the detector and of the features of physics events, in order to produce a realistic set of simulated events. In this paper, the software tools used to produce neutrino and cosmic ray signatures in the telescope and the strategy developed to represent the time evolution of the natural environment and of the detector efficiency are described.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cosmic ray experiments; Neutrino astronomy; Neutrino detectors; Neutrino experiments

Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J.-J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Physical Review D, 2020)
The ANTARES detector is an undersea neutrino telescope in the Mediterranean Sea. The search for pointlike neutrino sources is one of the main goals of the ANTARES telescope, requiring a reliable method to evaluate the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect with the ANTARES detector. The shadow is the deficit in the atmospheric muon flux in the direction of the Sun caused by the absorption of the primary cosmic rays. This analysis is based on the data collected between 2008 and 2017 by the ANTARES telescope. The observed statistical significance of the Sun shadow detection is 3.7 sigma, with an estimated angular resolution of 0.59 degrees +/- 0.10 degrees for downward-going muons. The pointing accuracy is found to be consistent with the expectations and no evidence of systematic pointing shifts is observed.
CRIS-Team WoS Importer:2021-01-15

Studying bioluminescence flashes with the ANTARES deep-sea neutrino telescope - Reeb, Nico; Hutschenreuter, Sebastian; Zehetner, Philipp; Ensslin, Torsten; Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; et al. (Limnology and Oceanography-Methods, 2023)
We develop a novel technique to exploit the extensive data sets provided by underwater neutrino telescopes to gain information on bioluminescence in the deep sea. The passive nature of the telescopes gives us the unique opportunity to infer information on bioluminescent organisms without actively interfering with them. We propose a statistical method that allows us to reconstruct the light emission of individual organisms, as well as their location and movement. A mathematical model is built to describe the measurement process of underwater neutrino telescopes and the signal generation of the biological organisms. The Metric Gaussian Variational Inference algorithm is used to reconstruct the model parameters using photon counts recorded by photomultiplier tubes. We apply this method to synthetic data sets and data collected by the ANTARES neutrino telescope. The telescope is located 40 km off the French coast and fixed to the sea floor at a depth of 2475 m. The runs with synthetic data reveal that we can model the emitted bioluminescent flashes of the organisms. Furthermore, we find that the spatial resolution of the localization of light sources highly depends on the configuration of the telescope. Precise measurements of the efficiencies of the detectors and the attenuation length of the water are crucial to reconstruct the light emission. Finally, the application to ANTARES data reveals the first localizations of bioluminescent organisms using neutrino telescope data.
CRIS-Team Scopus Importer:2023-10-20